Do markets overreact: International evidence - Baytas, Ahmet; Cakici, Nusret (Journal of Banking & Finance, 1999)
In this paper, using the Conrad and Kaul's methodology we test for the overreaction hypothesis – which maintains that stock prices systematically overshoot and therefore their reversal can be predicted from past performance — in seven industrialized countries. Consistent with the findings of Conrad and Kaul, we see no evidence of overreaction in the US. However, returns to long-term contrarian strategies in other countries seem to be generally significant. Moreover, we find that in the majority of the countries, while returns to arbitrage portfolios based on price are higher than those based on size, the latter generally outperform the winner–loser arbitrage portfolios.